Relating hydraulic conductivity and hyporheic zone biogeochemical processing to conserve and restore river ecosystem services - Mendoza-Lera, Clara; Datry, Thibault (The Science of the total environment, 2017)
River management practices commonly attempt to improve habitat and ecological functioning (e.g. biogeochemical processing or retention of pollutants) by restoring hydrological exchange with the hyporheic zone (i.e. hyporheic flow) in an effort to increase mass transfer of solutes (nutrients, carbon and electron acceptors such as oxygen or nitrate). However, even when hyporheic flow is increased, often no significant changes in biogeochemical processing are detected. Some of these apparent paradox result from the simplistic assumption that there is a direct relationship between hyporheic flow and biogeochemical processing. We propose an alternative conceptual model that hyporheic flow is non-linearly related with biogeochemical processing. Based on the different solute mass transfer and area available for colonization among hydraulic conductivities, we hypothesize that biogeochemical processing in the hyporheic zone follows a Gaussian function depending on hyporheic hydraulic conductivity. After presenting the conceptual model and its domain of application, we discuss the potential implications, notably for river restoration and further hyporheic research. [Display omitted] •Restoration attempts to increase biogeochemical processing by increasing hyporheic flow.•However, biogeochemical processing does not always increase with hyporheic flow.•Hyporheic flow and biogeochemical processing relationship is likely nonlinear.•Our alternative model: a saturating model as a function of hydraulic conductivity.•This approach may improve the success of hyporheic restoration efforts.